2021
DOI: 10.1186/s12916-021-02137-8
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Sustainable Development Goals for South African adolescents from high HIV prevalence areas: a longitudinal path analysis

Abstract: Background Adolescents experience a multitude of vulnerabilities which need to be addressed in order to achieve the Sustainable Development Goals (SDGs). In sub-Saharan Africa, adolescents experience high burden of HIV, violence exposure, poverty, and poor mental and physical health. This study aimed to identify interventions and circumstances associated with three or more targets (“accelerators”) within multiple SDGs relating to HIV-affected adolescents and examine cumulative effects on outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Our data clearly show that different outcomes may require different combinations of protective factors, which is in accordance with what has been found in previous accelerator studies [e.g., 8,11,17,28]. The pattern emerging from the current data seems to suggest that two to three protective factors can often provide a substantial boost, while additional factors provide for marginal gain and diminishing returns.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Our data clearly show that different outcomes may require different combinations of protective factors, which is in accordance with what has been found in previous accelerator studies [e.g., 8,11,17,28]. The pattern emerging from the current data seems to suggest that two to three protective factors can often provide a substantial boost, while additional factors provide for marginal gain and diminishing returns.…”
Section: Plos Onesupporting
confidence: 92%
“…Importantly, the UNDP SDG Accelerator and Bottleneck assessment distinguishes between accelerators, defined as life circumstances/ protective factors that directly influence SDG outcomes (e.g., food security or good parenting), and interventions, which can drive progress on access to these accelerators (e.g., feeding or parenting programmes) [10]. Evidence using observational data has identified a range of protective factors and their combinations (accelerator synergies) that bolster multiple outcomes for children and adolescents and can thus contribute to the accelerator model: safe schools [8], good parenting/parenting support [8,11], cash transfers [12], food security [11][12][13], living in a safe community [12,13], good mental health [14], education, ICT access [15], no survival work, small family size, food security, health extension [16], healthy caregivers [17] and access to community-based organisations [13]. There are now also programs emerging that are based on the idea of layered evidence-based services, such as the DREAMS programme, which aims to address the complex problem of high HIV incidences through a combined portfolio of provisions [18].…”
Section: Introductionmentioning
confidence: 99%
“…The accelerator approach has since been successfully applied in several studies (Cluver et al, 2020;Mebrahtu et al, 2021;Meinck et al, 2021). Of note, several of these studies have found positive effects of different accelerators on several indicators of mental health (Mebrahtu et al, 2021;Meinck et al, 2021). Building on such findings, the current study applies the accelerator approach to identify measures that may improve several, inter-related mental health outcomes simultaneously.…”
Section: Introductionmentioning
confidence: 96%
“…They found that three provisions (parenting support, government cash transfers, and safe schools) were associated with better outcomes across 11 SDG-aligned targets (Cluver et al, 2019). The accelerator approach has since been successfully applied in several studies (Cluver et al, 2020;Mebrahtu et al, 2021;Meinck et al, 2021). Of note, several of these studies have found positive effects of different accelerators on several indicators of mental health (Mebrahtu et al, 2021;Meinck et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the current study makes the first attempt to measure two unexplored dimensions of ontological security (violence and mental health), aligning them with SDG targets. Second, most studies focusing on accelerators used cross-sectional data and longitudinal data up to two time points (Chipanta et al, 2022;Cluver et al, 2019;Haag et al, 2022;Mebrahtu et al, 2021;Meinck et al, 2021). The current study is one of the first accelerator research using data from three time points, which could pose essential understanding of the long-term effects of consistent exposure to accelerators, enhancing their potential to be considered protective factors (Rudgard et al, 2022).…”
Section: Introductionmentioning
confidence: 99%